Limitations of Rural Health Services and Assessment Pregnant Mothers in the Pandemic Covid-19 of the Papua Province Indonesian - Irab, Semuel Piter (Advances in Social Sciences Research Journal, 2020)
Background Pandemic infectious diseases cause morbidity and deaths to increase over time globally. Corona virus disease-19 (Covid-19) is an infectious disease found in China in Wuhan City, and spread very quickly to Indonesia and Papua Province. The purpose of this study was to determine limitations of the rural health services, and assessment of the pregnant mothers in the pandemic covid-19 Papua Province of Indonesian. Methods The cross sectional study design, is a type of research to see the relationship between the limitations of rural health services, according to the assessment pregnant mothers in the pandemic covid-19 Papua Province. Jayapura City and Jayapura Regency research sites, which represents all Cities/Regencies in Papua Province. The population is all pregnant mothers in Jayapura City and Jayapura Regency. The samples was 89 pregnant mothers living in rural areas. Data analysis using the Chi-Square test (χ2). Results The limitation of integrated health service post was very less 38,2% and very good 22,5%. The community health center is very less 41,6% and good 22,5%. Hospitals are very less 31,5% and very good 25,8%. The practice of doctors / midwife is less 30,3% and very good 31,5%. The limitations of antenatal care were very less 38,2% and good 22,5%. The limitation treatment of the sick pregnant mothers was 39,3% and good 22,5%. The prevalence covid-19 rural is very high 40,4% and low 20,2%. Assessment of the significant pregnant mothers with prevalence covid-19 of rural, the limitations of integrated health service posts, community health centers, hospitals, doctor/midwife practices, limitations in pregnant mothers, and limitations of treatment for sick pregnant mothers. Conclusion The adverse effects of the pandemic covid-19 are increasing day by day, the provincial government of Papua implements health protocols to protect the public, in other parts of pregnant mothers who don’t suffer from corona virus, but suffering from other illnesses and wanting to visit a health service unit is limited.